2007
DOI: 10.1007/s11064-007-9443-5
|View full text |Cite
|
Sign up to set email alerts
|

Complex of Amyloid β Peptides with 24-Hydroxycholesterol and Its Effect on Hemicholinium-3 Sensitive Carriers

Abstract: Brains of Alzheimer disease patients in early stages of dementia contain an increased 24(S)-hydroxycholesterol (cerebrosterol)/cholesterol ratio when compared to controls. In this study, effects of amyloid beta peptides and of racemic 24-hydroxycholesterol were evaluated in vitro on undepleted or cholesterol-depleted hippocampal synaptosomes of young and old rats via a high-affinity choline transport and membrane anisotropy measurements. Depletion of membrane cholesterol decreased the transport of [3H]choline,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 47 publications
4
18
0
Order By: Relevance
“…However, it was not clear if the observed interactions between naturally occurring and brain originating 24(S)hydroxycholesterol (24(S)OH, known also as cerebrosterol) and Ab could be highly stereospecific (i.e., if they could reflect a possible physiological relevance) or if they could be rather nonspecific (which would be in agreement with our previous experiments showing the absence of marked differences in the interactions of non-aggregated or aggregated Ab with racemic 24-hydroxycholesterol see [25]). …”
Section: Introductionsupporting
confidence: 83%
See 3 more Smart Citations
“…However, it was not clear if the observed interactions between naturally occurring and brain originating 24(S)hydroxycholesterol (24(S)OH, known also as cerebrosterol) and Ab could be highly stereospecific (i.e., if they could reflect a possible physiological relevance) or if they could be rather nonspecific (which would be in agreement with our previous experiments showing the absence of marked differences in the interactions of non-aggregated or aggregated Ab with racemic 24-hydroxycholesterol see [25]). …”
Section: Introductionsupporting
confidence: 83%
“…Synaptosomes were prepared according to our previous study [25]. Briefly, the hippocampi were placed in ice-cold 0.32 M sucrose (10 ml/g tissue) and were homogenized with a glass-Teflon Potter's Braun homogenizer (10 upand down-strokes at 600 rpm).…”
Section: Preparations Of Undepleted or Cholesterol-depleted Synaptosomesmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous experiments on synaptosomes or cell cultures revealed that the disruption of lipid rafts using methyl-β-cyclodextrine treatment attenuated the HACU levels through a reduction in membrane-bound CHT1 and also through altered conformation. In addition, CHT1 from cholesterol-depleted synaptosomes appeared to be more vulnerable to Aβ actions [23,61]. Since perturbation of the lipid raft integrity are involved in AD pathogenesis [62], we suppose that the attenuated effects of some AChE inhibitors on CHT1 from cholesterol-depleted synaptic membranes (indicating, e.g., their stronger requirement to CHT1 conformation) should be advantageous with regard to AD therapy.…”
Section: Discussionmentioning
confidence: 99%